LEGO Mindstorms EV3 : the Mayan adventure - Bell, Mark (Middle School science teacher); Kelly, James F. (James Floyd) (Technology in action., 2017)
Through the use of a fictional story, this book details how to build and design robots. Although it offers numerous robotic designs and offers detailed information on how to build and program each robot, readers are encouraged to come up with their own.